Teoria środków produkcji materialnej a społeczeństwa współczesne - Kozyr-Kowalski, Stanisław (Wydział Prawa i Administracji UAM, 1982)
The above article belongs to the series of treatises aiminig at attributing such a form to categories and propositions of the historical materialism to make them become not only a mean of theoretical reflection on the m o d e r n societies but also a premise of field-empirical, sociological and economic research. The first part of the article is an attempt of the new interpretation of the proposition inherent in the historical materialism i.e. of "defining" a society as a whole (formation of a society) by its economic structure. Five basic processes, through which the "definition" of the social formation by its economy is carried into effect, are quoted there, as well as five theoretical and methodological functions performed by the respective sub-theories of the theory of the economic structure in examining economy ais a whole and a society as a whole. The arguments presented in the second part of the article are in favor of a proposition that the understanding of the part played by economy in the formation of a society advocated by the historical materialism is still not obsolete but it can also help to disclose that a majority of categories presently applied in the analysis of interactions between economy and non-economical structures is biased with the theoretical archaism and the Robinsonian approach. All the categories of the theory of means of material production analyzed in the article are serving to criticize and positively overcome the above mentioned bias; these are: "material labor", "objects of labor", "direct and indirect means of the material labor", "mental means of the material production", typology of conditioning processes presented within the structure of means of material production. The following concepts are considered to bear the traits of the theoretical archaism and the Robinsonian approach: "manual labor", "mental work", "instruments of labor", as well as other concepts identifying the means of production with a set of material objects and the powers of production with the means of production.
The Theory of Means of Material Production and the Modern Societies